Analysis Effectiveness Printed Media and Visual Media on the Knowledge of Hygiene Workers About Basic Life Assistance in Cardiac Arrent Events at Provita Hospital, Jayapura City, Papua - Dosinaeng, Antonius Satrio Wicaksono; Zainuri, Agus; Yogodly, Arius; Tingginehe, Rosmin Mariati (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the effectiveness of print media and visual video media on janitors' knowledge of basic life support in cardiac arrest at Provita Hospital, Jayapura City. This type of research is quantitative using Pre-Experiment method with Pre-test and Post-test method. The number of samples was 20 respondents, each of whom was asked questions before and after the intervention using print media and visual videos to see the comparison of the effectiveness of changes in knowledge. The results of the study of the two methods on increasing knowledge before and after the intervention obtained a ρ value of 0.001 <0.05 (α) with an average difference between the print media method of 85.30 and visual video of 77.20 with an IK value of 95%. The print media method is more effective in increasing knowledge about the concept of heart massage in cardiac arrest patients compared to the visual video media method. The conclusion in this study is that there is an effect of increasing knowledge through print media and visual videos about the basic concepts of heart massage in cardiac arrest patients at Provita Hospital Jayapura City, Papua Province.